Insights into life-history traits of Munidopsis spp. (Anomura: Munidopsidae) from hydrothermal vent fields in the Okinawa Trough, in comparison with the existing data. (June 2015) - Nakamura, Masako; Chen, Chong; Mitarai, Satoshi
Abstract: Squat lobsters in the genus Munidopsis are commonly found at, and near, hydrothermal vents. However, the reproductive traits of most Munidopsis spp. are unknown. This study examined the reproductive features of two Munidopsis species sampled from hydrothermal vent fields in the southern Okinawa Trough in February 2014. Three ovigerous females were collected: two Munidopsis ryukyuensis at Irabu Knoll (1661–1675 m depth) and one M. longispinosa at Hatoma Knoll (1482 m depth). Carapace sizes and egg volumes were measured and compared with those of other Munidopsis species. The ovigerous M. ryukyuensis specimens had postorbital carapace lengths of 10.3 and 11.8 mm, without the rostrum, and carapace widths of 8.6 and 9.7 mm. Mean egg volumes of M. ryukyuensis and M. longispinosa were ~4 mm 3 . These results are consistent with early sexual maturity in M. ryukyuensis and lecithotrophic development in both species, as described in other species of the genus. These life-history traits may enable these vent species to maximize their reproductive and dispersive potential. Highlights: Three ovigerous Munidopsis spp. females were found in the Okinawa Trough. M. ryukyuensis showed early sexual maturity with less than 10 mm in carapace width. Egg volumes were about 4 mm 3, implying the lecithotrophic development. M. longispinosa was larger and held 73 eggs of about 4 mm 3 in volume. Large egg yolk could provide sufficient food reserve for long-distance dispersal.